2018
DOI: 10.1007/s40430-018-1105-9
|View full text |Cite
|
Sign up to set email alerts
|

Tensile and impact characterization of S-glass/epoxy composite laminates containing microscale borax, perlite, and sewage sludge ash particles

Abstract: In this study, influences of microscale particles (borax, perlite, and sewage sludge ash) on tensile and impact resistances of S-glass/epoxy composite laminates were experimentally investigated. During the production of test samples, epoxy resin was modified incorporating them it inorganic and waste fillers at different weight ratios (0, 5, 10, 15, and 20% for borax, and 1, 2, 5, and 10% except for perlite). Damage mechanisms and impact properties of particle-modified composites were characterized by charpy im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 29 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…To sum up, this improvement of tensile and flexural properties was attributed to the chemical compatibility of the OP particles with epoxy resin and S-glass fibers in the composite laminate system. However, excessive addition of the OP particles detracted the chemical compatibility resulting in poor interfacial strength between matrix and particle and fiber interfaces as a result of aggregation [20][21][22].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…To sum up, this improvement of tensile and flexural properties was attributed to the chemical compatibility of the OP particles with epoxy resin and S-glass fibers in the composite laminate system. However, excessive addition of the OP particles detracted the chemical compatibility resulting in poor interfacial strength between matrix and particle and fiber interfaces as a result of aggregation [20][21][22].…”
Section: Mechanical Propertiesmentioning
confidence: 99%
“…The experimental results revealed that the application of low-temperature treatment improved the mechanical characteristics. Bulut et al 14 analyzed the influence of fillers on mechanical characteristics of S-glass/epoxy composite laminates. They found that incorporating fillers into the epoxy resin increased the mechanical characteristics of composites.…”
Section: Introductionmentioning
confidence: 99%